2018
DOI: 10.1098/rspb.2018.0367
|View full text |Cite
|
Sign up to set email alerts
|

Artificial light at night decreases metamorphic duration and juvenile growth in a widespread amphibian

Abstract: Artificial light at night (ALAN) affects over 20% of the earth's surface and is estimated to increase 6% per year. Most studies of ALAN have focused on a single mechanism or life stage. We tested for indirect and direct ALAN effects that occurred by altering American toads' () ecological interactions or by altering toad development and growth, respectively. We conducted an experiment over two life stages using outdoor mesocosms and indoor terraria. In the first phase, the presence of ALAN reduced metamorphic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The authors concluded that these choices are likely to affect the survival of both species as salamanders must choose a substrate of lower nutritional quality while frogs become more exposed to nocturnal predators. In field experiments, nocturnal LED light (Blue/green spectrum and intensities consistent with those found under street light) reduced larvae metamorphosis duration and juvenile growth in the American toad Anaxyrus americanus (Dananay and Benard, 2018). In addition ALAN also affected periphyton biomass, as mentioned before (section "Breeding").…”
Section: Frogssupporting
confidence: 68%
“…The authors concluded that these choices are likely to affect the survival of both species as salamanders must choose a substrate of lower nutritional quality while frogs become more exposed to nocturnal predators. In field experiments, nocturnal LED light (Blue/green spectrum and intensities consistent with those found under street light) reduced larvae metamorphosis duration and juvenile growth in the American toad Anaxyrus americanus (Dananay and Benard, 2018). In addition ALAN also affected periphyton biomass, as mentioned before (section "Breeding").…”
Section: Frogssupporting
confidence: 68%
“…In mice, dim continuous ALAN has been demonstrated to increase the rhythmic expression of core circadian genes associated with changes in feeding time and increased body mass gain (Fonken et al 2013). Similar ALAN-induced alteration in biological functions has also been revealed in invertebrates (Czaczkes et al 2018), fishes (Khan et al 2018), amphibians (Dananay & Benard 2018) and reptiles (French et al 2018).…”
Section: Introductionmentioning
confidence: 77%
“…Few reviews on ALAN effects on amphibians are available [70][71][72], and several recent studies investigated the effects of ALAN on amphibians. ALAN decreased metamorphic duration and juvenile growth in American toads (Anaxyrus americanus) [73], and reduced activity and altered energy allocation in common toads (Bufo bufo) [74]. Furthermore, a shift and shortening of the calling season of male Brazilian anurans was measured in a light-polluted wetland as compared to a similar site without light pollution [75].…”
Section: Amphibiansmentioning
confidence: 92%